2008
DOI: 10.1094/mpmi-21-4-0404
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of ENOD8 in Medicago truncatula Nodules Directs ENOD8 Esterase to Developing and Mature Symbiosomes

Abstract: In Medicago truncatula nodules, the soil bacterium Sinorhizobium meliloti reduces atmospheric dinitrogen into nitrogenous compounds that the legume uses for its own growth. In nitrogen-fixing nodules, each infected cell contains symbiosomes, which include the rhizobial cell, the symbiosome membrane surrounding it, and the matrix between the bacterium and the symbiosome membrane, termed the symbiosome space. Here, we describe the localization of ENOD8, a nodule-specific esterase. The onset of ENOD8 expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…2, A and B, arrows). Similar to endogenous MtENOD8, observed using immunolocalization (Coque et al, 2008), MtENOD8-GFP is found in proximal symbiosomes, but not in those in the distal zones of the nodule (Supplemental Fig. S1).…”
Section: Localization Of Mtenod8-gfp To the Symssupporting
confidence: 66%
See 3 more Smart Citations
“…2, A and B, arrows). Similar to endogenous MtENOD8, observed using immunolocalization (Coque et al, 2008), MtENOD8-GFP is found in proximal symbiosomes, but not in those in the distal zones of the nodule (Supplemental Fig. S1).…”
Section: Localization Of Mtenod8-gfp To the Symssupporting
confidence: 66%
“…1 and 2; Coque et al, 2008). Normally, the MtENOD8 protein is found highly expressed in some, but not all symbiosomes: Mature symbiosomes with elongated bacteroids contain MtENOD8, whereas younger, distal, infected nodule cells do not express it; this occurs because MtENOD8 is expressed in the proximal parts of nodules (Coque et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these proteins, carbohydrate esterases (CEs) play key roles in making other CAZymes access their carbohydrate substrates by removing acetyl groups from substituted saccharides with various chain lengths [5,6]. In the physiological aspect, CEs are considered to be involved in the formation of cell walls, interactions between host and microbes, and energy metabolism pathways [7][8][9][10][11][12][13][14][15]. CEs are also important for biotechnological application, as modifications of carbohydrates are necessary for the preparation of biofuel, drug carriers, and cosmetics [16][17][18].…”
Section: Introductionmentioning
confidence: 99%